Memprediksi Niat Wisatawan Memilih Street Food Menggunakan Theory of Reasoned Action - Vita Briliana; Keni Keni (Universitas Tarumanagara, 2022)
The importance of the role of culinary street food is now growing, by reviewing the attractiveness of street vendors to tourists and their untapped potential. This study aims to test the application of the Theory of Reasoned Action (TRA) in predicting the intention to choose street food among tourists in Bali. A structured questionnaire was used to obtain responses from 300 tourists using a purposive sampling technique with the PLS statistical method. The results prove that TRA is a valid model for predicting the intention to choose street food. Attitude, subjective norm, and perceived behavioral control were found to have a positive effect on the intention to choose street food. Compared to other variables, subjective norms have the most influence on the intention to choose street food. Pentingnya peran makanan kuliner street food kini semakin berkembang, dengan mengulas daya tarik pedagang kaki lima bagi wisatawan dan potensi yang belum tergali. Penelitian ini bertujuan menguji penerapan Theory of Reasoned Action (TRA) dalam memprediksi niat untuk memilih jajanan pinggir jalan (street food) di kalangan wisatawan di Bali. Kuesioner terstruktur digunakan untuk memperoleh tanggapan dari 300 wisatawan dengan menggunakan teknik purposive sampling dengan metode statistik PLS. Hasil membuktikan TRA merupakan model valid untuk prediksi niat memilih jajanan pinggir jalan. Attitude, subjective norm, dan perceived behavioral control ditemukan berpengaruh positif dengan intention to choose street food. Dibandingkan variabel lain, subjective norm paling berpengaruh terhadap intention to choose street food.